The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00384-015-2247-1
|View full text |Cite
|
Sign up to set email alerts
|

CD93 gene polymorphism is associated with disseminated colorectal cancer

Abstract: PurposeCluster of differentiation 93 (CD93) is involved in apoptosis and inflammation and has a suggested role in angiogenesis, and all of which are involved in the development and dissemination of cancer. We evaluated the expression of CD93 and the association with two single nucleotide polymorphisms (SNPs), rs2749812 and rs2749817, as possible biomarkers in colorectal cancer (CRC).MethodsTissue levels and plasma levels of CD93 were measured using an enzyme-linked immunosorbent assay (ELISA). Expression of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
(46 reference statements)
4
31
0
Order By: Relevance
“…Olsen RS et al had revealed that high expression of CD93 in colorectal cancer (CRC) was associated with two single nucleotide polymorphisms (SNPs, rs2749812 and rs2749817) and it could be a possible biomarker in CRC [33]. Chevrier S et al had reported that CD93 was an important molecular for the maintenance of plasma cells in bone marrow niches [34].…”
Section: Discussionmentioning
confidence: 98%
“…Olsen RS et al had revealed that high expression of CD93 in colorectal cancer (CRC) was associated with two single nucleotide polymorphisms (SNPs, rs2749812 and rs2749817) and it could be a possible biomarker in CRC [33]. Chevrier S et al had reported that CD93 was an important molecular for the maintenance of plasma cells in bone marrow niches [34].…”
Section: Discussionmentioning
confidence: 98%
“…cancer-specific death (Olsen et al, 2015), which is in agreement with other cancer studies (Langenkamp et al, 2015, Bao et al, 2016.…”
Section: N: N-terminus; S: Signal Peptide; Ctld: C-type Lectin-likesupporting
confidence: 82%
“…It has also been associated with different types of cancer such as breast cancer (Lee et al, 2009), glioblastoma (Langenkamp et al, 2015), CRC (Olsen et al, 2015) and nasopharyngeal carcinoma (Bao et al, 2016). In relation to cancer, CD93 has been associated with the risk of developing cancer (Lee et al, 2009).…”
Section: N: N-terminus; S: Signal Peptide; Ctld: C-type Lectin-likementioning
confidence: 99%
See 1 more Smart Citation
“…It is also highly expressed on the tumour‐associated vasculature. In a recent example, elevated levels of CD93 expression were detected on human colorectal carcinoma sections . Interestingly, this study also examined soluble levels of CD93 within patient plasma and found a 30% reduction in colorectal carcinoma patients compared with healthy controls.…”
Section: Cd93mentioning
confidence: 76%